2013
DOI: 10.1002/ieam.1459
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of riverine load of contaminants to european seas under policy implementation scenarios: An example with 3 pilot substances

Abstract: An evaluation of conventional emission scenarios is carried out targeting a possible impact of European Union (EU) policies on riverine loads to the European seas for 3 pilot pollutants: lindane, trifluralin, and perfluorooctane sulfonate (PFOS). The policy scenarios are investigated to the time horizon of year 2020 starting from chemical-specific reference conditions and considering different types of regulatory measures including business as usual (BAU), current trend (CT), partial implementation (PI), or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Although trifluralin is relatively persistent, it is gradually degraded in soil by microorganisms with a degradation half-life of less than 1 year ( US Environmental Protection Agency (EPA), 1996 ; Ribas et al., 1996 ; Gebel et al., 1997 ; Waite et al., 2004 ; Bouvier et al., 2006 ; Kang et al., 2008 ; Triantafyllidis et al., 2010 ). Nevertheless, trifluralin can be detected in the Arctic environment owing to sufficiently high quantities that are globally used and the long-range atmospheric transport that most likely occurs ( Marinov et al., 2013 ). Trifluralin, which had been a very prominent drug for half a century, was eventually banned in the European Union in 2008, owing to its toxicity to aquatic and human life ( UN Economic Commission for Europe (UNECE), 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although trifluralin is relatively persistent, it is gradually degraded in soil by microorganisms with a degradation half-life of less than 1 year ( US Environmental Protection Agency (EPA), 1996 ; Ribas et al., 1996 ; Gebel et al., 1997 ; Waite et al., 2004 ; Bouvier et al., 2006 ; Kang et al., 2008 ; Triantafyllidis et al., 2010 ). Nevertheless, trifluralin can be detected in the Arctic environment owing to sufficiently high quantities that are globally used and the long-range atmospheric transport that most likely occurs ( Marinov et al., 2013 ). Trifluralin, which had been a very prominent drug for half a century, was eventually banned in the European Union in 2008, owing to its toxicity to aquatic and human life ( UN Economic Commission for Europe (UNECE), 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early animal studies suggested trifluralin was not carcinogenic or teratogenic and that it had low toxicity, but later studies have shown that trifluralin can impact mitochondrial function, it has hormonal activity, , and it associates with higher cancer incidence rates in exposed agricultural workers . Trifluralin was ranked in the top five most hazardous pesticides of public health concern in a recent U.S.-specific study, and it has been banned in the European Union (EU) since 2008 due to concerns over its toxicity . An acceptable operator exposure level of 26 μg kg –1 day –1 has been determined for workers .…”
Section: Introduction: Chemistry Usage and Toxicity Of Trifluralinmentioning
confidence: 99%
“…17 Trifluralin was ranked in the top five most hazardous pesticides of public health concern in a recent U.S.-specific study, 18 and it has been banned in the European Union (EU) since 2008 due to concerns over its toxicity. 19 An acceptable operator exposure level of 26 μg kg −1 day −1 has been determined for workers. 20 Inhalation of either volatilized or atmospheric particulate-bound trifluralin is the most likely exposure pathway for humans.…”
mentioning
confidence: 99%